HUBUNGAN TINGKAT KECEMASAN PERPISAHAN DENGAN ORANG TUA TERHADAP MOTIVASI BELAJAR SANTRI KELAS VII DI MADRASAH TSANAWIYAH ULUMUL QUR’AN PAGAR AIR - Edy Cahyady; Mursyida Mursyida (Jurnal Sains Riset, 2021)
Background: Teenage anxiety is still high in Indonesia. Data from Riskesdas states that the National Prevalance of Anxiety Disorders of teenagers in Indonesia are about 37 thousand of the population with the mean age of 15 years. Separation anxiety is supposed to be a situation in which individuals become fearful and anxieous while being away from their parents. This emotional condition does not have a specific object. Anxiety is a factor that affects motivation, because a person who experiences anxiety will have obstacles to complete their work or to reach their goal. The aim of this study is to determine the relationship between level of separation anxiety between students and their parents towards students’ study motivation, in this case, year 7 students of Madrasah Tsanawiyah Ulumul Qur’an Pagar Air. Method: The method used in this research is an analytic quantitative with a cross-sectional design. The sampling technique used to obtain the sample in this research is random sampling which amounted to 86 respondents from year 7students of Madrasah Tsanawiyah Ulumul Qur’an Pagar Air. The research instrument that was used is a questionnaire about separation anxiety and a questionnaire about study motivation. The analysis data in this research is using Chi Square Hypothesis Test with the P. value of ɑ 0,05. Results: The results demonstrates that the majority of respondents have hight levels of separation anxiety (57,0%) and have a low level of study motivation (52,3%). Conclusion: The statistic test results demonstrates that there is a significant relationship between level of separation anxiety with their parents towards their motivation to studying, of year 7 students of Madrasah Tsanawiyah Ulumul Qur’an Pagar Air with the-value = 0,021 and ɑ = 0,05.Keywords: Separation anxiety, Study motivation, Teenage,Boarding school